2020
DOI: 10.3991/ijet.v15i18.15169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Blood Transfusion Course Using a Blended Learning Approach on the Acquisition of Clinical Reasoning Skills among Nursing Students in Morocco

Abstract: learning clinical reasoning skills in nursing education is a challenge for teachers and students. This study investigated the effects of a blended learning program on the acquisition of clinical reasoning skills via a blood transfusion course. The study employed a two group randomised controlled design with an experimental group (group 1, 16 students) and a control group (group 2, 16 students) recruited from a population of second-year nursing students at the Mohamed VI University of Health Sciences in Casabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Lack of face-to-face interactions between students and educators was considered to be a challenge by many participants of this study, corroborating findings from several other studies. [5,10,46,47] However, the finding that with BL, students may experience difficulties in courses that have practical or hands-on components is unique to this study as no other study reported this previously from the accessed literature. Despite the challenges experienced by students with the BL approach, participants in this study were more positive with the approach than with traditional face-to-face teaching.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Lack of face-to-face interactions between students and educators was considered to be a challenge by many participants of this study, corroborating findings from several other studies. [5,10,46,47] However, the finding that with BL, students may experience difficulties in courses that have practical or hands-on components is unique to this study as no other study reported this previously from the accessed literature. Despite the challenges experienced by students with the BL approach, participants in this study were more positive with the approach than with traditional face-to-face teaching.…”
Section: Discussionmentioning
confidence: 81%
“…[5] Another study found that students who were instructed using BL were able to perform blood transfusion procedures more effectively than those with face-to-face only. [10] BL, when implemented in nursing and midwifery professional courses, has been shown to improve nursing and midwifery skills, mostly Objective Structured Clinical Examination (OSCE), [11] and helped in the achievement of learning outcomes. [12] As the implementation of BL in educational programs increases, it is imperative to assess how students perceive this new and advanced way of teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies applied online education, one study utilized video‐based virtual reality‐based experiential flipped learning (SVVR‐EFL), 33 and one combined online education with an in‐person simulation 7 . All studies reported positive impact of e‐learning in comparison to other modalities of education based on learners' perspective on learning achievement 16,26,33 and assessment results 7,8,22,27,30,33 …”
Section: Resultsmentioning
confidence: 99%
“…To solve nursing problems, students will need to go through the clinical reasoning process, which includes analyzing the patient's situation through a comprehensive cognitive process (formal and informal thinking strategies) and evaluating the patient's health information to consider an alternative therapy (Barratt, 2018;Simmons, 2010). According to several previous studies' findings, BL can improve students' clinical reasoning skills by helping students to transition faster from memorizing simple knowledge to being able to provide a more comprehensive level of analysis (Gouifrane et al, 2020). This method also allows students to develop their logical thinking and hone their reasoning skills (Giraldo-Garcia, Roy, & Alotebi, 2015).…”
Section: Discussionmentioning
confidence: 99%